2016
DOI: 10.18632/oncotarget.13789
|View full text |Cite
|
Sign up to set email alerts
|

MiR-433-3p suppresses cell growth and enhances chemosensitivity by targeting CREB in human glioma

Abstract: Previous studies reported that miR-433 exerts function widely in human tumorigenesis and development. Here, we further investigate the potential role of miR-433 in glioma. Quantitative real-time PCR demonstrated that miR-433-3p and miR-433-5p were low expressed in glioma tissues and cell lines. Functional studies suggested that the overexpression of miR-433-3p suppressed proliferation, induced apoptosis and inhibited invasion and migration of human glioma cells. But the growth and metastasis of glioma cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Increased evidence has confirmed this idea that circular RNA‐ZFR inhibited cell proliferation and promoted apoptosis in gastric cancer by sponging miR‐130a/miR‐107 and modulating PTEN, circ‐ITCH inhibited bladder cancer progression by sponging miR‐17/miR‐224 and regulating p21 and PTEN expression, and hsa_circ_0046701 promoted carcinogenesis by increasing the expression of miR‐142‐3p target ITGB8 in glioma . Furthermore, hsa_circ_0008344 may bind to several miRNAs, such as miR‐433‐3p and miR‐450b‐3p, predicted by bioinformatics, while miR‐433‐3p has been found to suppress cell growth and enhance chemosensitivity by targeting CREB in glioblastoma . Accordingly, it is presumed that hsa_circ_0008344 can sponge tumor suppressor miRNAs followed by disinhibition of the expression of some targeted oncogenic genes, which contributes to glioblastoma progression.…”
Section: Discussionmentioning
confidence: 88%
“…Increased evidence has confirmed this idea that circular RNA‐ZFR inhibited cell proliferation and promoted apoptosis in gastric cancer by sponging miR‐130a/miR‐107 and modulating PTEN, circ‐ITCH inhibited bladder cancer progression by sponging miR‐17/miR‐224 and regulating p21 and PTEN expression, and hsa_circ_0046701 promoted carcinogenesis by increasing the expression of miR‐142‐3p target ITGB8 in glioma . Furthermore, hsa_circ_0008344 may bind to several miRNAs, such as miR‐433‐3p and miR‐450b‐3p, predicted by bioinformatics, while miR‐433‐3p has been found to suppress cell growth and enhance chemosensitivity by targeting CREB in glioblastoma . Accordingly, it is presumed that hsa_circ_0008344 can sponge tumor suppressor miRNAs followed by disinhibition of the expression of some targeted oncogenic genes, which contributes to glioblastoma progression.…”
Section: Discussionmentioning
confidence: 88%
“…Decreased miR-433 expression levels are correlated with distant metastasis and pathological TNM stage in patients with gastric cancer (21). MiR-433 downregulation has also been reported in colorectal cancer (22), hepatocellular carcinoma (23,24), myeloproliferative neoplasms (34), oral squamous cell carcinoma (35), ovarian cancer (36), retinoblastoma (37) and glioma (38). Conversely, miR-433 is overexpressed in osteosarcoma (39).…”
Section: Discussionmentioning
confidence: 95%
“…Li et al (37) indicated that miR-433 overexpression notably suppresses cell growth and metastasis and promotes cell cycle arrest and apoptosis in retinoblastoma. In addition, Sun et al (38) reported that restoring miR-433 expression prohibits cell proliferation and motility in vitro, induces apoptosis in vitro, reduces tumor growth in vivo and increases the chemosensitivity of cells to temozolomide in vitro and in vivo. However, miR-433 has been identified as an oncogene in osteosarcoma by regulating cell apoptosis and growth both in vitro and in vivo (39).…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐127 was reported to promote GBM cell migration and invasion by targeting tumor‐suppresser gene SEPT7 . MiR‐433 was reported to be commonly dysregulated in GBMs and suppressed glioma cell proliferation, migration, invasion, and enhanced sensitivity to TMZ therapy . Regarding miR‐759 and miR‐1248, no biological or clinical evidences have been reported in cancers so far.…”
Section: Discussionmentioning
confidence: 99%